2005
DOI: 10.1097/01.pgp.0000170067.73452.72
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to the Early Detection of Endocervical Adenocarcinoma

Abstract: We observed that the ratio of in situ to invasive carcinomas of the cervix is significantly greater for squamous than for glandular lesions. We wondered whether Pap smears were less effective for the identification of in situ glandular lesions. The purpose of this study was to determine if the location, extent of disease, and growth patterns of endocervical adenocarcinomas influence the ability to detect malignant cells by Pap smears. Medical records, doctor's office records, and all pathology materials (repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…However, it has been shown that a significant number of cervical AC arise above the level of the transformation zone or growing beneath the surface sparing the surface mucosa. 15 These ACs may display an endophytic growth pattern, thus escaping cervical cytology.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that a significant number of cervical AC arise above the level of the transformation zone or growing beneath the surface sparing the surface mucosa. 15 These ACs may display an endophytic growth pattern, thus escaping cervical cytology.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with the decrease in squamous cell carcinoma (SCC) since the introduction of screening programmes (Bergstrom et al, 1999;Ronco et al, 2005;Kyndi et al, 2006). Studies have shown that Pap smears are less sensitive in detecting precursor lesions of AC than those of SCC (Etherington and Luesley, 2001;Schoolland et al, 2002;Kalir et al, 2005). This makes the incidence of AC less likely to be influenced by screening (Nieminen et al, 1995;Bergstrom et al, 1999).…”
mentioning
confidence: 99%
“…30 Fortunately, these tumors appear to be uncommon. Data from the current study indicate that hrHPV DNA testing accurately reflects the increased cross-sectional risk of LSIL and HSIL in women whose Pap tests lack an EC/TZS.…”
mentioning
confidence: 99%